Evaluation of banana (Musa sp.) flowers of selected varieties for their antioxidative and anti-hyperglycemic potentials - Marikkar, Jalaldeen Mohammed Nazrim; Tan, S. J.; Salleh, Abu Bakar; Azlan, Azrina; Mohamad Ali, Mohd Shukuri (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Consumption of banana flower as a vegetable is popular among many countries in Southeast Asia. In this study, banana flowers of six different Malaysian cultivars namely, pisang Abu (Musa balbisiana cv P. Abu), pisang Berangan (Musa acuminata cv P. Berangan), pisang Nipah (Musa balbisiana cv P. Nipah), pisang Susu (Musa acuminata cv P. Susu), pisang Mas (Musa acuminate cv P. Mas) and pisang Rastali (Musa paradisiaca cv P. Rastali) were investigated for their antioxidant and anti-hyperglyemic properties. The total poly phenolic content and antioxidant activities, the α-amylase and α-glucosidase inhibitory potentials of the banana flower extracts were studied in vitro using relevant assays. Among the six cultivars, cultivar Susu was found to have the highest phenolic content (80.13 ± 4.64 mg of GAE/g of extract) and displayed the highest ABTS+ and DPPH radical scavenging activities (24.73 ± 0.04 and 25.10 ± 0.15 μmole of Trolox equivalent/g of extract). The anti-amylase and antiglucosidase activity of the banana flowers extracts were in the range of 47.31-62.58% and 74.98-91.62%, respectively. All banana flower extracts inhibited the activity of α-glucosidase better than α-amylase at the concentration of 200 μg/ml. This study concluded that the extracts of Malaysian banana flowers were potent sources of natural antioxidants, which can be used as postprandial hyperglycemia regulators.